2013
DOI: 10.1007/s00221-013-3791-y
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral tactile masking between forearms

Abstract: Masking effects have been demonstrated in which tactile sensitivity is affected when one touch is close to another on the body surface. Such effects are likely a result of local lateral inhibitory circuits that sharpen the spatial tuning of a given tactile receptor. Mutually inhibitory pathways have also been demonstrated between cortical tactile maps of the two halves of the body. Occasional reports have indicated that touches on one hand or forearm can affect tactile sensitivity at contralateral locations. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This is known as long-range tactile masking (Sherrick, 1964; Braun et al, 2005; Tamè et al, 2011) and seems to indicate a precise connection between the representations of certain patches of skin. For example, the sensitivity to touch on one arm can be influenced by long-range masking only by touch on the corresponding point on the other arm (Figure 6A; D’Amour and Harris, 2014a). Likewise touches on the stomach can be affected by simultaneous touch on the corresponding part of the back (Figure 6B; D’Amour and Harris, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is known as long-range tactile masking (Sherrick, 1964; Braun et al, 2005; Tamè et al, 2011) and seems to indicate a precise connection between the representations of certain patches of skin. For example, the sensitivity to touch on one arm can be influenced by long-range masking only by touch on the corresponding point on the other arm (Figure 6A; D’Amour and Harris, 2014a). Likewise touches on the stomach can be affected by simultaneous touch on the corresponding part of the back (Figure 6B; D’Amour and Harris, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…By varying the position of the limbs relative to each other, we have demonstrated that long-range tactile masking also depends on the position of the limbs in space (D’Amour and Harris, 2014a). Such modulation by posture suggests that long-range tactile masking is a phenomenon at or beyond the point at which the postural body schema is derived rather than at or before the level of the primary somatosensory cortex.…”
Section: Introductionmentioning
confidence: 99%
“…This technique provides behavioural 5,7,8,[13][14][15] evidence to support neurophysiological [16][17][18] and neuroimaging data [19][20][21][22][23] that suggest that the integration of somatosensory inputs from the two sides of the body occurs in a somatotopic representation. In these experiments, the effect of arm location was briefly examined by comparing masking when the hands were touching or parallel.…”
Section: Discussionmentioning
confidence: 63%
“…Analyses of the data was reported in 13 . Tactile sensitivity (expressed relative to the thresholds measured in the control condition) on the forearm was significantly reduced (thresholds were significantly increased) when vibrotactile masking stimulation was applied to the opposite arm (Figure 2A), demonstrating a contralateral masking effect between forearms.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Long-range tactile masking has been reported between mirror symmetric points on the hand and arm (that is, touch at a particular point on one limb has effects specifically at that same point on the other limb, Sherrick 1964;Braun et al 2005;Tamè et al 2011;D'Amour and Harris 2014a) and between the front and back of the body (D'Amour and Harris 2014b). These studies reveal unexpected connections between distantly separated parts of the body suggesting a nonlinear arrangement of the body representation.…”
Section: Introductionmentioning
confidence: 97%